Outcome and recurrence 1 year after pediatric arterial ischemic stroke in a population‐based cohort. Issue 5 (5th April 2016) - Mallick, Andrew A.; Ganesan, Vijeya; Kirkham, Fenella J.; Fallon, Penny; Hedderly, Tammy; McShane, Tony; Parker, Alasdair P.; Wassmer, Evangeline; Wraige, Elizabeth; Amin, Sam; Edwards, Hannah B.; Cortina‐Borja, Mario; et al.
Abstract : Objective: Arterial ischemic stroke (AIS) is an important cause of acquired brain injury in children. Few prospective population‐based studies of childhood AIS have been completed. We aimed to investigate the outcome of childhood AIS 12 months after the event in a population‐based cohort. Methods: Children aged 29 days to < 16 years with radiologically confirmed AIS occurring over a 1‐year period residing in southern England (population = 5.99 million children) were eligible for inclusion. Outcome was assessed during a home visit using the Pediatric Stroke Outcome Measure (PSOM). Parental impressions of recovery were assessed using the Pediatric Stroke Recurrence and Recovery Questionnaire. PSOM score was estimated via telephone interview or clinician interview whenever home visit was not possible. Results: Ninety‐six children with AIS were identified. Two children were lost to follow‐up. Nine of 94 (10%) children died before the 12‐month follow‐up. One child had an AIS recurrence. PSOM scores were available for 78 of 85 living children at follow‐up. Thirty‐nine of 78 (50%) had a good outcome (total PSOM score < 1), and 39 of 78 (50%) had a poor outcome. Seizures at onset of AIS were associated with a poor outcome (odds ratio = 3.5, 95% confidence interval = 1.16–10.6). Twenty‐eight of 73 (38%) children were judged by their carers to have fully recovered. Ten of 84 (12%) children had recurrent seizures, and 17 of 84 (20%) reported recurrent headaches. Interpretation: AIS carries a significant risk of mortality and long‐term neurological deficit. However, the rates of mortality, recurrence, and neurological impairment were markedly lower in this study than previously published figures in the United Kingdom. Ann Neurol 2016;79:784–793